Import prices and pricing-to-market effects in the euro area - Thomas Warmedinger (European Central Bank (ECB), 2004)
Pricing-to-market (PTM) behaviour implies that exporters adjust their prices to the prevailing prices in their export markets. For the importing country, PTM effects can be interpreted as a measure of the stability of domestic prices against foreign price and exchange rate developments. PTM behaviour can be attributed to the level of competitiveness and price stickiness in the importing country. This paper investigates PTM behaviour in the euro area from the importing country's perspective, for both individual countries and the euro area as a whole. Analysis firstly involves the estimation of PTM effects in the five largest euro area countries. Secondly, PTM effects in the euro area as a whole are estimated to be slightly higher than one half. The results from illustrative simulations suggest that the increase in euro-area inflation during the first two years of monetary union can be largely attributed to oil price and exchange rate developments.
Keywords: C32; E31; F14; F47; 330; euro area; exchange-rate pass-through; import prices; pricing-to-market